Soundscape and subjective factors affecting residents’ evaluation of aircraft noise in the communities under flight routes - Qu, Fei; Li, Zhuoming; Zhang, Tongtong; Huang, Wenjun (Frontiers in Psychology, 2023)
Aircraft noise is one of the most significant sources of environmental pollution in large cities. During the COVID-19 pandemic, strict lockdown in community might increase residents' discomfort with the noise, which could disrupt public activities and reduce subjective well-being. Most of the existing studies considered aircraft noise as a single sound source, which have ignored the influence of other sounds in the community and non-acoustic factors. This paper applying field survey in three communities under the flight route to identify the factors related to aircraft noise, community activities, attitudes, and socio-economic covariates that influence the evaluation of aircraft noise and general health. The results indicated that the negative effects of aircraft noise were enhanced during the lock down, especially for frequent space users and those residents in poor health status. The study also provided support for the moderating effects of natural sounds on resident’s noise evaluation. Under conditions of similar levels of aircraft noise exposure, communities with more birdsong and fountain sounds had lower proportion of highly annoyed respondents and higher level of soundscape ratings. This paper further indicated that personal factors including fear of air travel, noise sensitivity, and the frequency of outdoor activity had increased the level of annoyance to aircraft noise, while higher degree of annoyance to aircraft noise was associated with poor health status. The findings can inform aircraft noise control and community consultation strategies by protecting vulnerable populations and creating community soundscape facilities.